Primary cutaneous amyloidosis of the glans penis. Two case reports and a review of the literature. (1st March 2014) - Merika, E.E.; Darling, M.Ι.; Craig, P.; Paul, M.; Francis, N.; Lachmann, H.; Porter, W.; Bunker, C.B.
Summary: Background: Primary cutaneous amyloidosis of the penis is a rare entity. Objectives: We describe two cases of primary penile cutaneous amyloidosis presenting as localized lesions on the penis and not associated with systemic amyloidosis. Methods: A comprehensive literature review of all published cases. Results: The rarest form of cutaneous amyloidosis, nodular amyloidosis, is the most frequent presentation of penis‐limited cutaneous amyloid with a low incidence of systemic disease progression. Conclusions: Although primary nodular amyloidosis is a rare entity it seems to be the most frequent presentation of penile‐limited cutaneous disease, with a low incidence of systemic involvement.